Harmonizing Regional Spatial Arrangements As Effort To Improve Law Number 11 Of 2020 On Job Creation To Optimize Regional Development - Agus Tri Widodo; Agus Riwanto (Jurnal Dinamika Hukum, 2023)
After the Constitutional Court Decision Number 91/PUU-XVIII/2020 which mandates amendments to Law Number 11 of 2020 on Job Creation, it has consequences for the government to make improvements to the said law within a period of two years from the issuance of the decree. In Law Number 11 of 2020 on Job Creation, there are inconsistencies in the regulation of the form of legal products used for stipulation, norms for detailed spatial planning as a licensing instrument, and the existence of formal aspects that were ruled out at the time of its formation, causing polemics in the community. This article discusses how to implement spatial planning arrangements in the regions and how ideal harmonization spatial planning arrangements in order to optimize regional development. The research method to answer these problems is normative legal research that uses primary legal materials and secondary legal materials complemented by field research. The results of the study show that first, the spatial planning arrangements contained in Law Number 11 of 2020 concerning Job Creation cannot be implemented optimally, especially in terms of fostering and supervising the use of regional space. Second, it is necessary to improve the substance of the material as a material aspect in the form of setting detailed spatial plans with the suitability of space utilization activities and the stipulation of regional regulations by the central government. and improvement of formal aspects to minimize polemics in the community. Spatial planning is the main guideline in regional development.Keywords: Harmonization, Spatial Planning, and Regional Development